PENGARUH FATHERLESS DENGAN MARITAL ATTITUDE PADA DEWASA AWAL PENGGUNA TIKTOK DAN INSTAGRAM - Risma Firliana Aan Innayah; Itto Nesyia Nasution; Rini Hartati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The phenomenon of fatherless in Indonesia is increasingly gaining attention alongside rising rates of father absence within families. Growing up without a father figure, whether physically or psychologically, potentially influences how individuals perceive marriage, referred to as marital attitude. This study aims to examine the influence of fatherless on marital attitude among emerging adults who use TikTok and Instagram. A total of 270 respondents were selected using a purposive sampling technique, consisting of 101 males (37.4%) and 169 females (62.6%) aged 18–40 years, unmarried, and using TikTok or Instagram for a minimum of two hours per day. The research instruments used were the Fatherless Scale, developed based on Lamb et al.'s (2017) aspects, and the General Attitudes Toward Marriage Scale (GATM), adapted from Park and Rosen (2013). The study employed a quantitative approach with simple linear regression analysis. Hypothesis testing results showed a significance value of 0.000 (p < 0.05), thus the hypothesis was accepted. A correlation coefficient of R = 0.425 indicates a moderate positive relationship, with a coefficient of determination R² = 0.181, meaning fatherless contributed 18.1% to the formation of marital attitude. These findings indicate that the higher the level of fatherless experienced, the greater its impact on emerging adults' marital attitude, particularly in the context of exposure to marriage-related content on TikTok and Instagram.